METHODOLOGY OF VOLLEYBALL LESSON AND TECHNOLOGICAL FUNDAMENTALS - Boltayev, Azam (Журнал иностранных языков и лингвистики, 2023)
This article describes the initial and main purpose of the teaching process, teaching techniques, stages and tools of the teaching process. Determining, monitoring, and evaluating the effectiveness of methods, tools, and learning technologies used at different stages of the learning process is one of the key requirements of a multi-year sports training system. In this article enlightened primary and main aim of teaching period, teaching techniques, degrees and tools of teaching process. And specify teaching techniques results and using methods and resources in various stages of teaching. The main requirements of annual sport preparing are assessment and analyzed the methodology of the volleyball lesson.